2018
DOI: 10.1007/s10997-018-9410-3
|View full text |Cite
|
Sign up to set email alerts
|

Agency conflicts, executive compensation regulations and CEO pay-performance sensitivity: evidence from Sweden

Abstract: Based on a unique country set up with concentrated ownership of firms, strong representation of major shareholders on boards and one of the highest percentages of firms with dual-class shares worldwide I study CEO pay-performance sensitivity in Swedish listed firms in the years 2001-2013. Focusing on Type II agency conflict, I find that that pay-performance sensitivity in family-controlled firms with family CEOs is significantly lower than in other types of firms, and that dual-class firms have significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…The P–P lens suggests that controlling families of business groups (Chang, 2003; Morck et al, 2005) may exploit minority shareholders. Our robust results that compared to their professional counterparts, family CEOs experience higher pay which is unaffected by poor firm performance and is disproportionately boosted by superior firm performance, is consistent with the P–P lens and is the opposite of prior findings on CEO compensation in family firms in mature economies like the United States (Gómez‐Mejía et al, 2003) or Sweden (Cieślak, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…The P–P lens suggests that controlling families of business groups (Chang, 2003; Morck et al, 2005) may exploit minority shareholders. Our robust results that compared to their professional counterparts, family CEOs experience higher pay which is unaffected by poor firm performance and is disproportionately boosted by superior firm performance, is consistent with the P–P lens and is the opposite of prior findings on CEO compensation in family firms in mature economies like the United States (Gómez‐Mejía et al, 2003) or Sweden (Cieślak, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…Other studies, albeit in different contexts, have identified a nonsignificant effect (Combs et al, 2010) or even a positive effect (Barontini & Bozzi, 2018; Gallego & Larrain, 2012) of family ownership on CEO compensation. Some research has suggested that CEOs of family firms who are also members of the family receive lower compensation than those who are externally hired professionals (Barontini & Bozzi, 2018; Block, 2011; Cieślak, 2018; Gomez‐Mejia et al, 2003; Michiels et al, 2013; Young & Tsai, 2008). However, Combs et al (2010) showed that this effect only held if the CEO was a family member serving in a firm together with other family representatives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most studies of executive compensation in family firms have relied on market‐based theories, such as agency theory and the notion of optimal contracting (Barontini & Bozzi, 2018; Cheung & Chan, 2004; Cieślak, 2018; Combs et al, 2010; Croci et al, 2012; De Cesari et al, 2016; Gomez‐Mejia et al, 2003; Jaskiewicz et al, 2017; Michiels et al, 2013). For example, Combs et al (2010) suggested that in family firms, members of the family exercise strategic control over CEOs' actions, thereby alleviating the agency problem between owners and CEOs and reducing the likelihood of rent expropriation by family CEOs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Institutional investors and external blockholders also have power and ability to monitor managerial decisions related to strategic decisions of organisation including CEO compensation (Shin-Ping and Hui-Ju, 2011). Similarly, Cieślak (2018) observed that if the firm ownership is concentrated among family members, it is less likely that CEOs are paid excessive compensation. Hence, the present study also argues that effective corporate monitoring (internal and external) are helpful in better governing and controlling the opportunistic behaviour of top management which might influence the level of CEO compensation extracted on the cost of shareholders' wealth maximisation principle.…”
Section: Introductionmentioning
confidence: 97%